Pencegahan Dini Stunting Melalui Edukasi Anemia Pada Remaja Putri - Nabilah Nurul Ilma; Hasri Yulianti; Martina Fenansia Diaz (Health Care : Journal of Community Service, 2024)
Nutrition is crucial for human development, benefiting physical growth, cognitive development, and individual productivity. However, malnutrition, particularly stunting and anemia, remains a significant obstacle to achieving sustainable development goals. Research has established a close link between stunting in children and maternal anaemia, particularly in developing countries. This highlights the importance of preventing anemia in adolescent girls and women of childbearing age to combat stunting in children. Preventing stunting requires not only nutritional interventions but also behavior changes within communities through effective education. A community service activity was conducted to enhance the knowledge of adolescent girls in preventing anemia and early stunting. The activity involved counseling sessions and pre-test and post-test questionnaires. The results showed a significant increase in knowledge among the adolescent girls, with a 65% increase in good knowledge and a 40% decrease in poor knowledge. Developing a strong understanding of anaemia as an early preventive measure is crucial for reducing stunting prevalence in the future.